An Easily Overlooked Contamination of Syringes in Newborn Screening by Tandem Mass Spectrometry - Wang, Yanyun; Sun, Yun; Jiang, Tao (Frontiers in Pediatrics, 2021)
Background: Tandem mass spectrometry becomes a common and important test in newborn screening, but potential contamination of the equipment is largely ignored. Methods: The source of contamination through Biosan quality control samples was examined prospectively, and further confirmed by retrospective analysis of patient samples. Results: We found that the source of contamination came from syringe by Biosan quality control samples. Furthermore, we found that a large number of indicators in patient sample were interfered by syringe contamination in our center, and also in two other newborn screening centers, but the affected indicators were different in different screening centers. Conclusion: Syringe contamination will affect the detection of patient samples by tandem mass spectrometry, and should be monitored carefully and immediately.